(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Hydrokinetic turbines extract energy from tidal, marine, and riverine currents but must be able to withstand the harsh ocean environment. While turbines are often designed and optimized assuming uniform inflow conditions, hydrokinetic turbines must be able to withstand non-uniform and time-varying conditions. The effect of waves produces a time-varying non-uniform inflow on hydrokinetic turbines. These wave effects can cause unsteady variations in the thrust, torque, and spanwise hydrodynamic loading of the turbine blades. The design process must account for these effects to ensure turbine reliability, structural integrity, and cost-effective power generation. Computational Fluid Dynamics (CFD) is a useful tool to model the complex hydrodynamics of hydrokinetic turbines and the effect of waves on hydrokinetic turbines. CFD can accurately model the flow over the rotor and also the wake effects downstream of the turbine. To accurately model the effect of waves on hydrokinetic turbines, the nonlinear wave-current interaction must be accounted for, and the waves must be accurately propagated through the fluid domain. The objective of the present study is to parametrically investigate the effect of waves on the performance, unsteady loading, and wake effects of a hydrokinetic turbine using CFD. The current study presents a novel parametric investigation of regular wave effects on hydrokinetic turbines by systematically examining the impact of varying wave heights and wavelengths. Additionally, the interaction between wave and current directions is explored under both opposing and following conditions. The analysis is performed on a model scale turbine and the computations are performed using the OpenFOAM platform.